Sowing date of palisadegrass intercropped with grain sorghum and soybean yield in succession - Dias, Danyllo Santos; Umburanas, Renan Caldas; Sena Junior, Darly Geraldo de (Comunicata Scientiae, 2018)
The use of intercropping sorghum-palisadegrass for grain and straw production has become an advantageous cultivation option, can provide improvements in physical and chemical soil properties, maximizes production and income to the growers. There are still many management gaps to be improved in this intercropping in order that grower has the best outcome. Considering this, the objective of this study was to evaluate different sowing dates of palisadegrass in relation to sorghum, and evaluate the yield of soybean cultivated in succession. Palisadegrass was sown in monocrop and also between the lines of sorghum at different times (0, 15 and 25 days after sowing sorghum), as well the sorghum in monocrop. Soybeans were grown in succession on the straw of the mentioned treatments. It was evaluated biomass production and grain yield. Sowing palisadegrass and sorghum on the same day reduced sorghum grain yield and the palisadegrass biomass production. However, if palisadegrass are sowed 15 days after sorghum sowing, did not reduce the sorghum grain yield. Also, if the producer aims to produce sorghum grains, it is better to delay the sowing of palisadegrass in relation to sorghum. Although, if the producer aims to produce residual dry biomass, it is better to sow palisadegrass on the same day as sorghum or monocrop palisadegrass. Soybean yield did not differ among treatments when grown on different straws in the first year of cultivation.